The tail of the timberwolf - Quill, Penumbra (My little pony. Ponyville mysteries ;, 2017)
"Sweetie Bell and the other Cutie Mark Crusaders can't wait for Zipporwhill's birthday party! When the big day arrives, things are going great, that is ... until an angry Timberwolf appears! But where did the Timberwolf come from in the first place? And why did it seem more interested in candy than in any of the ponies? The Cutie Mark Crusaders are on the case, and their new friend, Lilymoon, has a hunch they're dealing with a werepony--a pony who turns into a Timberwolf! Can the gang solve the case in time and save whoever this poor pony is?"--Page 4 of cover.